Antimicrobial and Structural Properties of Metal Ions Complexes with Thiosemicarbazide Motif and Related Heterocyclic Compounds - Namiecińska, Ewelina; Sobiesiak, Marta; Małecka, Magdalena; Guga, Piotr; Rozalska, Barbara; Budzisz, Elzbieta (Current Medicinal Chemistry, 2019)
Antibiotic resistance acquired by various bacterial fungal and viral pathogens poses therapeutic problems of increasing severity. Among the infections that are very difficult to treat, biofilm-associated cases are one of the most hazardous. Complex structure of a biofilm and unique physiology of the biofilm cells contribute to their extremely high resistance to environmental conditions, antimicrobial agents and the mechanisms of host immune response. Therefore, the biofilm formation, especially by multidrugresistant pathogens, is a serious medical problem, playing a pivotal role in the development of chronic and recurrent infections. These factors create a limitation for using traditional chemiotherapeutics and contribute to a request for development of new approaches for treatment of infectious diseases. Therefore, early reports on antimicrobial activity of several complexes of metal ions, bearing thiosemicarbazide or thiosemicarbazones as the ligands, gave a boost to worldwide search for new, more efficient compounds of this class, to be used as alternatives to commonly known drugs. In general, depending on the presence of other heteroatoms, these ligands may function in a di-, tri- or tetradentate forms (e.g., of N,S,-, N,N,S-, N,N,N,S-, N,N,S,S-, or N,S,O-type), which impose different coordination geometries to the resultant complexes. In the first part of this review, we describe the ways of synthesis and the structures of the ligands based on the thiosemicarbazone motif, while the second part deals with the antimicrobial activity of their complexes with selected metal ions.
Keywords: structures of metal ions complexes